Emotional Card guna Meningkatkan Keceriaan dalam Pelafalan Bunyi Bahasa “Fon” Vokal pada Pembelajaran Fonologi - Nuraini, Cut (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to determine the effect of using learning media in the form of “Emotion Punctuation Cards” that combine emotion symbols (facial expressions) and punctuation marks for the process of pronouncing vowel sounds related to the level of cheerfulness when learners (students of the Phonology Course) pronounce phonetic vowel sounds. A quasi-experimental method with a pre-test and post-test kontrol group design was used on 40 Indonesian Language and Literature Education students at FKIP UNSIKA. The results showed that the experimental group using “Emotion Punctuation Cards” experienced a significant increase in the process of pronouncing the correct phonetic vowel sounds and the level of cheerfulness compared to the kontrol group. Implications for teaching phonetic vowel sounds and mood are discussed